That all shall be saved: (re?)discovering and sharing apokatastasis as the “gospel sung in eschatological key” in the Dutch Reformed Church - de Bruin, Dieter (Stellenbosch Theological Journal, 2023)
Central to the question of evangelism in the Southern African context is to “begin again at the beginning” of what exactly the gospel is and what it entails. This article contends that any formulation of the gospel of “the living Lord Jesus Christ …” that envisions even the possibility of the notion of hell as eternal separation from God, annihilation, or punishment for anyone is not “good” news at all, but is in fact, as one writer in the South African context puts it: “the bad news of the Gospel.” Moreover, holistic, or missional conceptions of eschatology, such as that of the influential New Testament Scholar N.T. Wright, inasmuch as they reject or do not explicitly accept universal salvation, lack theological coherence, and cannot be inculcated and shared as good news in the Southern African context. The Dutch Reformed Church and the ecumenical church urgently need to (re)discover the doctrine of ??????????????? for its rediscovery of evangelism not to be in vain.